Who do you know, where? Social investments in faraway contacts. (August 2018) - Chua, Vincent; Axhausen, Kay W.; Tan, Teresa
Abstract: It takes some effort to build and maintain a spatially diverse network, so why do people continue to cultivate them? The usual explanations draw on the biographical details of individuals, their age, their work and educational histories, their access to communication and transportation affordances, and so on. Using social capital theory and empirical evidence based on the personal networks of some 410 Singaporean respondents, this study finds a positive correlation between a spatially diverse network and access to high-status network members. This could suggest that social capital, the resources embedded in an individual's social network, constitutes a powerful motivation behind the cultivation of a spatially diverse network.